Online Promotions Strategy Through the PESO Model Approach on Instagram @akkarjuicebar in Increasing the Number of Consumers in 2025 - Delviana Farah Dini Safitri; Adhianty Nurjanah; Denis Hida Lutfiana Stefani (Jogjakarta Communication Conference (JCC), 2026)
Changes in modern society’s lifestyle shows a significant shift toward healthier living patterns. This study aims to analyze the online promotion strategy through the PESO model approach on the Instagram @akkarjuicebar in increasing the number of consumers in 2025. Akkar juice bar is business that sells healthy fruit-based beverages and relies on Instagram as its primary promotional medium. This research uses a descriptive qualitative method with data collection techniques through in-depth interviews and documentations. The study applies the PESO model proposed by Gini Dietrich. The results show that Instagram promotion conducted by akkar juice bar aims to reach a wider range of consumers while introducing the brand identity to new audiences, the target consumers are individuals aged 19-35 years, particulary students and workers who are concerned about a healthy lifestyle. The implementation of the PESO model includes the use of Paid media through endorsments by Instagram creators @belindapermata and @putufahru. Earned media appears through consumers voluntarily activities in sharing their experiences, such as posting Instagram stories, uploading product photos, and tagging the account @akkarjuicebar. Shared media is implemented through interactive features including comments, direct massages, and reposting costumers’ stories. Owned media is realized through the management of the Instagram account @akkarjuicebar, wich is fully controlled by the Akkar team. This study shows that the PESO elements most relied upon are owned and earned media. However, their utilization still needs improvement so that they not only generate interaction but also encourage purchasing decisions more effestively.